Doctrinal origins of spetsnaz: Soviet submarine-inserted special operations in northern Scandinavia during World War Two. - Nordin, Per-Olof (Fort Leavenworth, KS : US Army Command and General Staff College, 2020)
During the 1930s, the Soviet Union began developing tactical and operational instructions for naval forces, describing that the Soviet Navy should be prepared for active-offensive actions from shore to enemy shore and bases. This was a task for the Soviet Navy in both peace and war, and preparations were a continuous effort, in order to bring the war back to the enemy as soon as possible. Some of the means to achieve this are the submarines, and the operational support of reconnaissance assets. The method is to use the submarines for deep penetration, in order to deliver effect in the form of fires, raiding parties, and agents. Before World War Two the Soviet Red Navy developed the first steps of amphibious assault, ranging from large assaults in support of ground forces operations, to insertions of agents. When the Red Navy was separated from the Red Army, this gained momentum, and soon the Naval Infantry was formed. During World War Two, the Soviet Union developed special operations forces, amongst them submarine-inserted naval scouts, later to be knows as spetsnaz. These conducted operations against German convoys supporting the German-Finnish war in northern Scandinavia and Soviet Union. The first try to insert a larger force failed and instead focus was changed to scouts for reconnaissance missions, with occasional sabotage raids, which was more successful. The operations was not war winning, but tied up German forces and resources which could have been better used somewhere else. They proved invaluable, however, for the gaining of experience for and establishment of the Soviet naval special forces. The German Wehrmacht tried different methods to combat the reconnaissance parties. During 1942, they realized that the repeated attacks on their northern convoys must have been supported by enemy observation posts along the coast of Northern Norway. However, it was not until the capture of a Soviet soldier that they understood what to look for. A series of operations were conducted, ending with an operation to ...